Effect of Zoom fatigue on health and learning loss in students during the COVID-19 pandemic - Angga Aditya Permana; Adhi Kusnadi; Anggita Nauli Marpaung; Elisabet Dela Marcela; Natasya Yuasan; Syifa Fauziyah (Jurnal Inovasi Teknologi Pendidikan, 2023)
Covid-19 pandemic causes all face-to-face activities converted to distance or virtual meetings, including educational learning system. These days, the majority educational institutions in Indonesia still implement distance learning via video conference platforms. This primary research aims to discover how Zoom Fatigue affects health and causes learning loss in university students across Java. The methodologies used in this research are qualitative and quantitative. To specify this research, the population is set to students who study at several universities in Java, with 50 samples being Multimedia Nusantara University students and the other 50 sample are being students from other universities in Java. The techniques used to collect data are observation and questionnaire via Google Forms. After analyzing responses, the result shows that most students experience health issues such as eyesight issues, exhaustion, and saturation. Moreover, most students also go through some issues when it comes to the learning process, they experience a decrease of learning motivation and have trouble concentrating. Nevertheless, their academic records are stable and some even stated that their grades are increasing when compared to face-to-face learning systems, this fact shows that in-class learning is not the only source of information used by students to support their academic performance, but there are other sources of information such as internet where students can look up information from online article and scientific journals.